Mothers Against Drunk Driving recognition of Jack Cadman - Mothers Against Drunk Driving (Organization) (2003)
Jack Cadman was the first forensic pathologist to work in the Orange County, California criminal justice system. As part of his duties, he worked with Theron Johns of Beckman Instruments to find a way to measure blood alcohol levels using a gas chromatograph. One local newspaper was so impressed it wrote a song about this new crime-fighting method, to the tune of "Santa Claus is Coming to Town." Beckman Instruments entered the gas chromatograph business in 1956 with the acquisition of the successful Watts Manufacturing Company. Later that year, Beckman Instruments produced its first gas chromatograph, the GC-1, which was intended for laboratory use. Shortly after, Beckman Instruments produced a line of gas chromatographs for industrial use, which offered both automation and customization. These instruments were used by the petroleum industry and in the fight against air pollution.
Keywords: California--Orange County; Blood alcohol--Testing; Scientific apparatus and instruments; Gas chromatography--Forensic applications; Gas chromatography--Instruments; Beckman Instruments, Inc.